PECULIARITIES OF TEACHING THE DISCIPLINE "PERSPECTIVE AND SHADOWS" FOR STUDENTS OF DESIGN - ПРАСОЛ , С. І.; ХИНЕВИЧ , Р. В.; КОВАЛЬОВ , Ю. А.; ОВЧАРЕК , В. Є.; СКЛЯРЕНКО , В. О. (Art and Design, 2022)
Purpose: considers the peculiarities of teaching the discipline "Perspective and Shadows" with the involvement of paintings by famous artists of the Renaissance and Baroque, as well as presentations of consecutive execution of promising images. The significance of the analysis of works of art in the study of the discipline "Perspective and Shadows", the place of perspective in the general theory of images is determined. Methodology. Systematic and comparative analysis of paintings by artists of the Renaissance and Baroque periods, presentations of consecutive execution of perspective images are used. Results. Analysis of Renaissance and Baroque paintings made it possible to trace the development of aerial perspective as thinking in the artists of that time. Approaches to the analysis of perspective in the image of the object and the role of presentations of step-by-step construction of perspective in the formation of professionalism of the future designer are presented. It is determined that the comparative analysis of works of art of different periods is a necessary component of practical tasks for mastering the material in studying the discipline "Perspective and Shadows" and understanding the general laws of development and ways of applying geometric systems of perspective together with presentations. Scientific novelty. The role of the analysis of works of art of different historical periods for mastering of the materials of the discipline "Perspective and Shadows" is determined, the concept of using presentations of stages of construction of perspective images is laid down. Practical significance. The obtained results can be used in teaching the discipline "Perspective and Shadows" by students majoring in "Design" and in the identification of works of art by era.